Soil water dynamics and yield response of broccoli (Brassica oleracea) under drip irrigation with different irrigation frequency - SINGH, AMANDEEP; KUMAR, SANJAY; DHALOIYA, ARVIND; KUMAR, NARENDER; MOR, AMAN; KUMAR, ASHISH; DHANGER, PARVEEN; DAGAR, HARENDER (The Indian Journal of Agricultural Sciences, 2022)
Semi-arid region can benefit greatly from surface and subsurface drip irrigation techniques in overcoming the problem of water scarcity. Therefore, a field study was carried out at the research farm of CCS Haryana Agricultural University, Hisar, Haryana during winter (rabi) season 2019–20 and 2020–21 to investigate the effectiveness of surface and subsurface drip irrigation on growth and yield of broccoli (Brassica oleracia L.). Subsurface drip irrigation shows higher moisture content than surface drip irrigation at vertical as well as radial distance. The growth parameters were found highest in the treatment irrigation after one day under subsurface drip irrigation. The average highest (14610 kg/ha in 2019–20 and 14740 kg/ha in 2020–21) and lowest (12920 kg/ha in 2019–20 and 13030 kg/ha in 2020–21) total yield was recorded under irrigation after one day in subsurface drip irrigation and irrigation after three days in surface drip irrigation treatments, respectively. It is concluded that alternate days irrigation with subsurface drip irrigation gives better performance to obtain the maximum yield of broccoli grown in the semi-arid region of India.